Preliminary study on the cultivation mode of innovative talents in the first-class cyber security college - Tongge XU; Lianzhong LIU; Jianwei LIU; Jian MAO (网络与信息安全学报)
Cyberspace security is a matter of national security,and the talent cultivation is of top priority.Based on the experience of developing the first-class cyber security college of Beihang University,this paper analyzes some common issues,and discusses the ideas,mechanisms and patterns of cyberspace security talents cultivation from the aspects of the talents selection,curriculum system,comprehensive training platform,practical training and academic competitions.It may provide a reference for the training of cyber security professionals.